Dekonstruksi Ijtihad: Revitalisasi Kebekuan Nalar Melampaui Dogmatisme - Akmal Bashori (Syariati: Jurnal Studi Al-Qur'an dan Hukum, 2016)
One of the principal reasons for the failure of Muslims to reconcile Islam law is that the process of ijtihad was closed several centuries ago. However, the sacred texts of Islam need to be interpreted in the light of contemporary realities and modern knowledge. For ijtihad to be performed successfully in a society, democracy and freedom of expression must prevail. While scholars of Islamic law clearly have very important roles to play in the revived practice of ijtihad, they should not have exclusive responsibility over this practice. Faithfulness to the text needs to be combined with creative imagination to produce the most enlightened reinterpretations (decontruction), suitable for the twenty-first century. Muslim scholars have particular opportunities as well as a responsibility to lead a revival of ijtihad. Muslim scholars in the university have the freedom to think creatively while still being faithful to the texts, and their new interpretations could stimulate new thinking among the more traditional religious establishments.